resolva os sistemas a seguir utilizando o método da substituição:
Anexos:
![](https://pt-static.z-dn.net/files/d28/e7f2aa615c74a82a9c89dcd9481bb155.jpg)
Soluções para a tarefa
Respondido por
3
x + y = -1 y= (-1) - x
x + 5y = 3 y= (-1) - 3
x + 5.(-1 - x) = 3 y = 2
x + (-5) -5x = 3
6x - 5 = 3
x= 3 - 5
2/6 S = (3,2)
x=3
x + 5y = 3 y= (-1) - 3
x + 5.(-1 - x) = 3 y = 2
x + (-5) -5x = 3
6x - 5 = 3
x= 3 - 5
2/6 S = (3,2)
x=3
Perguntas interessantes
Administração,
11 meses atrás
Matemática,
11 meses atrás
Matemática,
1 ano atrás
Pedagogia,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás